Pengaruh variasi laju kendaraan dan beban muatan terhadap karakteristik emisi gas buang mesin diesel - Kurniawan Dwi Alfiyan; Ethys Pranoto; Riza Pahlevi Marwanto (Universitas Gunadarma, 2026)
This study aims to analyze the influence of variations in vehicle speed and payload on exhaust gas emission characteristics as well as combustion behavior in a diesel engine. Tests were conducted on a pickup vehicle with speed variations of 20, 30, 40, and 50 km/h and payloads of 0 kg, 587 kg, and 700 kg. The emission parameters analyzed include carbon monoxide (CO), hydrocarbons (HC), carbon dioxide (CO2), oxygen (O2), and smoke opacity, measured using a gas analyzer and smoke tester. The results show that increases in vehicle speed and load indicate a tendency in the combustion process from relatively stable conditions toward incomplete combustion, as indicated by significant increases in CO, HC, and opacity. The observed findings suggest a tendency toward over-fueling conditions at high loads, where increased fuel supply is not matched by adequate air supply in a naturally aspirated diesel engine, resulting in locally rich zones within the combustion chamber. This condition reduces combustion quality and increases the formation of incomplete oxidation products. The increase in CO₂ emissions reflects higher fuel consumption due to greater power demand, but does not necessarily indicate improved combustion efficiency. Meanwhile, relatively stable O₂ levels suggest that combustion inefficiency may be influenced by limitations in air–fuel mixing and reaction time, rather than a global oxygen deficiency. These results indicate an indirect decrease in energy conversion efficiency and an increase in pollutant emissions. Therefore, controlling vehicle operating conditions is important to improve energy efficiency and reduce diesel engine exhaust emissions.